A study on the association of serum lipid profile with retinal hard exudates among patients wim type 2 diabetes mellitus in Hospital USM - Amelah Mohamed, Abdul Qader (2008)
Retinal hard exudate is a component of diabetic retinopathy which is formed due to breakdown of the inner blood retinal barrier, as a process of microangiopathy. Objectives: To study the association between lipid profile and retinal hard exudates in diabetic retinopathy and the association between oxidized-LDL with systemic diseases among type 2 diabetic patients. Methodology: A cross sectional study was conducted in 40 patients with diabetic retinopathy and another 40 patients without diabetic retinopathy. Demographic data was collected and comprehensive ocular examination was performed. Nine ml venous blood was taken for fasting serum cholesterol, triglycerides, HDL, LDL, ox-LDL, and for HbAIC· Results: The mean serum cholesterol level was 5.9 (1.86) mmol/L in diabetic retinopathy group compared to patients without retinopathy 5.0 (1.03) mmoi/L (P= 0.001). The mean serum LDL was 3.6 (1.69) mmol/L in retinopathy group compared to 3.0 (1.02) mmoi!L in the contol group (P=0.005). There was a higher concentration of serum cholesterol, triglyceride and LDL in patients with severe retinal hard exudates compared to those with mild and moderate,however it was not statistically significant (P= 0.082, 0.116, 0.218) respectively. The mean serum oxidized-LDL concentration was higher in diabetic retinopathy with severe retinal hard exudates compared to mild and xi moderate. There was no statistically significant difference in the mean oxidized LDL with other systemic diseases or duration of diabetes. Conelusion: There was significant association between serum cholesterol and LDL with diabetic retinopathy. However there was no association between serum lipid profile with the severity of retinal hard exudates. Serum ox-LDL was also not associated with diabetic retinopathy and other systemic co-morbidities in our study.